Use of Nanomaterial-Based (Micro)Extraction Techniques for the Determination of Cosmetic-Related Compounds - José Grau; Juan L. Benedé; Alberto Chisvert (Molecules, 2020)
The high consumer demand for cosmetic products has caused the authorities and the industry to require rigorous analytical controls to assure their safety and efficacy. Thus, the determination of prohibited compounds that could be present at trace level due to unintended causes is increasingly important. Furthermore, some cosmetic ingredients can be percutaneously absorbed, further metabolized and eventually excreted or bioaccumulated. Either the parent compound and/or their metabolites can cause adverse health effects even at trace level. Moreover, due to the increasing use of cosmetics, some of their ingredients have reached the environment, where they are accumulated causing harmful effects in the flora and fauna at trace levels. To this regard, the development of sensitive analytical methods to determine these cosmetic-related compounds either for cosmetic control, for percutaneous absorption studies or for environmental surveillance monitoring is of high interest. In this sense, (micro)extraction techniques based on nanomaterials as extraction phase have attracted attention during the last years, since they allow to reach the desired selectivity. The aim of this review is to provide a compilation of those nanomaterial-based (micro)extraction techniques for the determination of cosmetic-related compounds in cosmetic, biological and/or environmental samples spanning from the first attempt in 2010 to the present.